Development of downstream processing to minimize beta‐glucan impurities in GMP‐manufactured therapeutic antibodies. (21st October 2016) - Vigor, Kim; Emerson, John; Scott, Robert; Cheek, Julia; Barton, Claire; Bax, Heather J.; Josephs, Debra H.; Karagiannis, Sophia N.; Spicer, James F.; Lentfer, Heike
Abstract : The presence of impurities or contaminants in biological products such as monoclonal antibodies (mAb) could affect efficacy or cause adverse reactions in patients. ICH guidelines (Q6A and Q6B) are in place to regulate the level of impurities within clinical drug products. An impurity less often reported and, therefore, lacking regulatory guideline is beta‐glucan. Beta‐glucans are polysaccharides ofd ‐glucose monomers linked by (1‐3) beta‐glycosidic bonds, and are produced by prokaryotic and eukaryotic organisms, including plants. They may enter manufacturing processes via raw materials such as cellulose‐based membrane filters or sucrose. Here we report the detection of beta‐glucan contamination of a monoclonal IgE antibody (MOv18), manufactured in our facility for a first‐in‐human, first‐in‐class clinical trial in patients with cancer. Since beta‐glucans have potential immunostimulatory properties and can cause symptomatic infusion reactions, it was of paramount importance to identify the source of beta‐glucans in our product and to reduce the levels to clinically insignificant concentrations. We identified beta‐glucans in sucrose within the formulation buffer and within the housing storage buffer of the virus removal filter. We also detected low level beta‐glucan contamination in two of four commercially available antibodies used in oncology. Both formulation buffers contained sucrose. We managed to reduce levels of beta‐glucan in our product 10‐fold, by screening all sucrose raw material, filtering the sucrose by Posidyne® membrane filtration, and by incorporating extra wash steps when preparing the virus removal filter. The beta‐glucan levels now lie within a range that is unlikely to cause clinically significant immunological effects. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:1494–1502, 2016